MAJOR TECHNIQUES OF ERROR CORRECTION IN ELT - Kulmanova Mahinur Anvar kizi (Web of Journals Publishing, 2023)
The article is intended to discuss types of error correction and main principles of it in order to improve learners knowledge in ELT classroom. , Error correction is a way to develop competence of language learners in a second or foreign language. It can be utilized for attaining knowledge of a second or foreign language, and in learning the language’s rules.
Keywords: errors, error correction, feedback, English language, ELT.